Investment Model for Traditional Villages in Bali as Tourism Village Managers - Putra, Komang Satria Wibawa; Astawa, I Nengah Dasi; Putra, Made Satria Pramanda (Institut Pariwisata dan Bisnis Internasional, 2022)
A traditional village is a traditional institution that has the authority to regulate all activities of indigenous peoples and non-indigenous people who are active and live in their territory.This study aims to analyze the form of business entity for traditional villages in Bali to managinga tourism village as well as models and forms of investment between traditional villages in Bali and investors for the development of tourism villages in their area. The type of research used is normative juridical legal research with statutory and conceptual approaches. The results of the study show that the form of business entity that can be formed by traditional villages in Bali in managing tourist villages in order to facilitate investment from investors is BUPDA in accordance with Bali Regional Regulation No. 4 of 2019. Then, the investment model between traditional villages in Bali and investors in the development of tourist villages is by making joint operation cooperation agreements and partnership cooperation agreements as well as agreements in the capital aspect with the condition that investors are not allowed to take all or part of BUPDA ownership as village managers tourism in accordance with Bali Regional Regulation No. 4 Year 2022.